The THE EFFECT OF THE ROLE OF HUMORS IN ADVERTISING AND ATTRACTION OF ADVERTISING MODELS ON INTEREST TO BUY CONSUMERS - Ramadhayanti, Ana (Fundamental Management Journal, 2019)
The products displayed in advertisements are products that have been designed by advertising companies both in terms of the attractiveness of the role of the model and the presentation of advertisements that commonly use the role of humor in advertising. The role of humor consists of words presented in advertisements, behaviors and communication styles. With the role of humor and the attractiveness of advertising models can attract consumer buying interest. However, to find out and prove it real, further research must be done. This research method uses research descriptive quantitative method by collecting data by distributing questionnaires. Based on the results of the study, it can be concluded that the Role of Humor in Advertising affects the Purchase Interest, while Attractiveness influences buying interest. Keywords: Role of Humor, Attractiveness, Ad Model, Buying Interest